ROUND TABLE ON THE TREND OF ACCOUNTING INSTRUCTION. (The Accounting Review, 1926)
Abstract The article presents information on the recent changes regarding the mode of instruction in Accounting. Among the matters considered were recent changes in courses that were given, developments in methods of Instruction, the possibility of granting a distinct degree in accounting and the possibility of the development of independent professional schools for students of accounting. It also presents a report by various committees on the trend of Accounting instruction. The report of the Committee on Publication Plan was presented by academician and chairman J. Hugh Jackson, and was adopted. Chairman W. I Goggin submitted the report of the Auditing Committee, with was duly accepted. G.A. MacFarland reported for the Resolutions Committee. Professor MacFarland included, informally, two resolutions which had been omitted in the report drawn up by the chairman of the Committee. One was a resolution of appreciation to the management of the Hotel McAlpin for the service rendered to the Association. The other was a resolution to extend greetings to professor Hatfield and to express regret that he was unable to attend the meetings.